Kajian Simulasi Dinamika Molekul Adsorpsi Hidrogen pada Carbone Nanotube dengan Variasi Chirality dan temperatur Menggunakan Kode LAMMPS - Erika Marinda Mufida; Sri Wahyu Suciyati; Gurum Ahmad Pauzi; Amir Supriyanto (Journal of Energy, Material, and Instrumentation Technology, 2021)
Hydrogen adsorption has been simulated on carbon nanotubes for optimum hydrogen absorption. Parameters that affect the amount of hydrogen absorbed have been studied, such as the effect of chirality and temperature on hydrogen absorption in CNTs. The simulation method of hydrogen adsorption on carbone nanotubes uses molecular dynamics simulation code LAMMPS, applies Lennard-Jones interatomic potential and hydrogen atom movement using Van Der Waals force with Microcanonical Ensemble. Data analysis is the output of LAMPS in the form of data in XYZ format. The data contains information in the form of integration steps, number of atoms, temperature, pressure, potential energy, kinetic energy, volume, van der Waals energy, total simulation time and hydrogen absorption. The simulation results show that the optimum absorption occurs at run 10000 and a temperature of 100 K, for armchair chirality of 10 atoms, chirality of 12 atoms and zigzag chrality of 5 atoms. Formation of hydrogen coordinates with Avogadro software, formation of CNT coordinates with VMD software and visualization of hydrogen adsorption on CNTs using VMD software.